2006
DOI: 10.1007/s10562-006-0016-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analytical Study of Two Pt–Rh Three-way Catalysts

Abstract: Pt-Rh three-way catalysts (TWCs) of two formulations were examined by electron probe microanalysis (EPMA) and cross sectional transmission electron microscopy (TEM), in order to study the effect of accelerated aging on microstructure. Both formulations have Pt and Rh applied in separate washcoat layers, Rh in a zirconia-rich outer layer and Pt in an alumina-rich inner layer(s). Microstructural analyses show that in spite of the initial separation, the precious metals inter-diffuse between the washcoat layers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Yu-Yao and Kummer [9]reported that they were able to prepare low concentration precious metal catalysts via vapor phase transport from a metal foil to an alumina or ceria-alumina support. The transport of precious metals has also been found to lead to formation of alloys and bimetallic nanoparticles, as in the case of physically mixed Pt and Pd [10] catalysts and also Pt, and Rh catalysts [11]. In this previous work, the results were influenced by the catalyst formulation, for example the same nominal ratio of Pt and Pd gave very different extent of volatilization and transport.…”
Section: Introductionmentioning
confidence: 97%
“…Yu-Yao and Kummer [9]reported that they were able to prepare low concentration precious metal catalysts via vapor phase transport from a metal foil to an alumina or ceria-alumina support. The transport of precious metals has also been found to lead to formation of alloys and bimetallic nanoparticles, as in the case of physically mixed Pt and Pd [10] catalysts and also Pt, and Rh catalysts [11]. In this previous work, the results were influenced by the catalyst formulation, for example the same nominal ratio of Pt and Pd gave very different extent of volatilization and transport.…”
Section: Introductionmentioning
confidence: 97%
“…Haaß and Fuess [1] reported on the deactivation mechanism of model automotive catalysts and their structural characterisation. Because an extrapolation from model catalysts to commercial TWCs is not always possible, an understanding of deactivation processes of real life TWCs is definitely mandatory [2,3]. First results of activity measurements and structural investigations of commercial TWCs will be presented.…”
Section: Introductionmentioning
confidence: 99%
“…We illustrate the construction of the substitution curve model for the TWC. Data were collected for PGM loading in 24 TWCs, described in the technical literature. , Loadings were normalized on the basis of engine displacement to a common engine size of 2.5 L.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected for PGM loading in 24 TWCs described in the technical literature. (40,(46)(47)(48)(49)(50)(51)(52) Loadings were normalized based on engine displacement to a common engine size of 2.5 liters.…”
Section: Overall Model Framework a Model Of Aggregate Automotive Pgm Usementioning
confidence: 99%